Bio301: A Web-Based EST Annotation Pipeline That Facilitates Functional Comparison Studies. (22nd November 2011) - Chen, Yen-Chen; Chen, Yun-Ching; Lin, Wen-Dar; Hsiao, Chung-Der; Chiu, Hung-Wen; Ho, Jan-Ming
Abstract : In this postgenomic era, a huge volume of information derived from expressed sequence tags (ESTs) has been constructed for functional description of gene expression profiles. Comparative studies have become more and more important to researchers of biology. In order to facilitate these comparative studies, we have constructed a user-friendly EST annotation pipeline with comparison tools on an integrated EST service website, Bio301. Bio301 includes regular EST preprocessing, BLAST similarity search, gene ontology (GO) annotation, statistics reporting, a graphical GO browsing interface, and microarray probe selection tools. In addition, Bio301 is equipped with statistical library comparison functions using multiple EST libraries based on GO annotations for mining meaningful biological information.